1996
DOI: 10.1073/pnas.93.24.14014
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism of action of tetracyclines: Effects on nitric oxide synthases

Abstract: Tetracyclines have recently been shown to have ''chondroprotective'' effects in inf lammatory arthritides in animal models. Since nitric oxide (NO) is spontaneously released from human cartilage affected by osteoarthritis (OA) or rheumatoid arthritis in quantities sufficient to cause cartilage damage, we evaluated the effect of tetracyclines on the expression and function of human OA-affected nitric oxide synthase (OA-NOS) and rodent inducible NOS (iNOS). Among the tetracycline group of compounds, doxycycline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
246
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(268 citation statements)
references
References 46 publications
11
246
0
4
Order By: Relevance
“…The production of both NO and PGE 2 by OA cartilage explants can be attenuated by inhibitors of protein synthesis (cycloheximide) and NF-B (PDTC). An interesting divergence in the regulation of COX-2 and NOS in chondrocytes, however, is reflected in their sensitivity to glucocorticoids: in OA chondrocytes expression of COX-2, but not NOS, is inhibited by prior exposure to dexamethasone (11,38).…”
Section: Discussionmentioning
confidence: 99%
“…The production of both NO and PGE 2 by OA cartilage explants can be attenuated by inhibitors of protein synthesis (cycloheximide) and NF-B (PDTC). An interesting divergence in the regulation of COX-2 and NOS in chondrocytes, however, is reflected in their sensitivity to glucocorticoids: in OA chondrocytes expression of COX-2, but not NOS, is inhibited by prior exposure to dexamethasone (11,38).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a previous study has reported that acyclovir blocks the expression of inflammatory cytokines (Halford et al 1997). Moreover, recent reports have shown that antibiotics such as minocycline or macrolides demonstrate antiinflammatory activity in addition to their known function (Amin et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, when doxycycline is present during activation of the proenzyme, MMPs are degraded into catalytically inactive fragments (33). In addition, doxycycline inhibits messenger RNA for inducible nitric oxide synthase, a potent stimulus for MMP production by chondrocytes (34).…”
Section: Lohmander Et Almentioning
confidence: 99%